MONITORING GOALKEEPERS’ PHYSIOLOGY USING MODERN WEARABLE DEVICES - Bobomuradov Sobitjon Erkinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the use of modern wearable devices to monitor the physiology of football goalkeepers. The study examines how wearable technologies, such as heart rate monitors, motion sensors, and biometric trackers, can provide real-time data on physical performance, fatigue levels, and recovery. Additionally, the article discusses the benefits of integrating wearable devices into training programs to optimize performance, prevent injuries, and support professional development.